2009
DOI: 10.1177/0013916509341244
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Influence on Human Landscape Preference

Abstract: Individuals residing in the rainforest belt of Nigeria were shown photographs of five biomes: rain forest, deciduous forest, coniferous forest, savanna, and desert. Subjects overwhelmingly selected savanna scenes as representing the most desirable place to live. These results, coupled with extensive American data, support the hypothesis that humans possess an innate preference for savanna-like settings, which then is modified through experience and enculturation. Findings are discussed in relation to anthropol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
119
1
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 204 publications
(133 citation statements)
references
References 40 publications
7
119
1
6
Order By: Relevance
“…It is for this reason that preferences drive decisions we make in life, such as, for instance, where we choose to live. Some studies have demonstrated that people tend to prefer parkland and savannah-like landscapes (Falk and Balling, 2010), and similar types of open, lightly wooded, green landscape have been idealised throughout human civilisation (Ward Thompson, 2010). When asked to categorise images of environments, some of the most consistent differentiation is between 'wild' and more ordered and managed landscapes (Hartig and Evans, 1993), suggesting that degree of human influence is relevant in people's responses.…”
Section: Links To Other Researchmentioning
confidence: 99%
“…It is for this reason that preferences drive decisions we make in life, such as, for instance, where we choose to live. Some studies have demonstrated that people tend to prefer parkland and savannah-like landscapes (Falk and Balling, 2010), and similar types of open, lightly wooded, green landscape have been idealised throughout human civilisation (Ward Thompson, 2010). When asked to categorise images of environments, some of the most consistent differentiation is between 'wild' and more ordered and managed landscapes (Hartig and Evans, 1993), suggesting that degree of human influence is relevant in people's responses.…”
Section: Links To Other Researchmentioning
confidence: 99%
“…Models developed by environmental psychology (Daniel 2001) have shown that the human perceptual system is a tool designed through evolution, which is concerned with both survival and adaptation to ecosystems. Many studies have shown how through history our innate biophilic tendencies have been strongly modulated by cultural influences to fit into particular ecological contexts, while generating strong feelings of identity (Falk and Balling 2010). When people were asked about the ecosystem services that they perceived as being supplied by different landscapes, their answers tended to be strongly influenced by their origin, demands, and world views.…”
Section: Usefulness Of Visual Enquiries As a Means Of Public Participmentioning
confidence: 99%
“…HAN (2003) showed this via a study in the six principal terrestrial biomes (desert, tundra, grassland, coniferous forest, deciduous forest, and Rainforest), establishing that those with highest valuation were coniferous forests and tundras, whereas this with lowest valuation were grasslands and deserts. But this has its nuances; FALK and BALLING (2010), in a study with inhabitants of the Nigerian forest belt, showed photographs of five biomes: tropical rainforest, deciduous forest, coniferous forest, savanna, and desert. The subjects mostly chose savanna as the most desirable place to live.…”
Section: The Love Of Water and Plantsmentioning
confidence: 99%